An analysis of using code mixing on interaction between homogeneous pair in collaborative writing - Veniati, Veniati; Indriati, Titin; Trionanda, Stevanus (Privietlab, 2025)
Code-mixing is a procedure that involves the insertion of components from one language into another. Therefore, this study aimed to identify the types of code-mixing utilized by the students in homogeneous pairing interaction in collaborative writing and investigate the frequencies of code-mixing used by the students in homogeneous pairing interaction in collaborative writing. In this study, a descriptive qualitative research approach was applied. Furthermore, the types and frequencies of code-mixing utilized by students in homogenous paired interaction in collaborative writing are the focus of this study. The subjects were fifth-semester students in Central Java, Indonesia. To collect data, the researchers used audio recordings of student interactions. In analyzing the data, the researchers used Hoffman’s (1991) theory on types of code-mixing. According to the findings, there are three types of code-mixing: intra-sentential code-mixing (28), intra-lexical code-mixing (29), and code-mixing requiring a change in pronunciation (30). (5). There are numerous types of code-mixing for each form. Thus, intra-lexical code-mixing is the most prevalent type of code-mixing in student interactions, while code-mixing involving a change in pronunciation is the least common.